2013
DOI: 10.1177/0011128713492499
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Virtual Time Spent Socializing With Peers, Substance Use, and Delinquency

Abstract: This study tests Osgood, Wilson, O'Malley, Bachman, and Johnston's extension of the routine activity theory of individual deviant behavior by considering adolescent time spent socializing with peers in virtual settings in relation to estimates of delinquency and substance use. The growth in digital communication has significantly changed the ways that youth commonly communicate with one another, and such changes may therefore provide a specification of newly emerging situational inducements that precipitate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 30 publications
6
38
1
1
Order By: Relevance
“…Finally, individuals embedded in small networks reported significantly fewer deviant acts and exposure to deviant behavior online compared to those in medium and large networks. This is consistent with the results of Meldrum and Clark (2013) who found that time spent socializing with online peers was associated with an increase in delinquent behavior.…”
Section: Effect Of Exposure Across Network Sizesupporting
confidence: 92%
See 4 more Smart Citations
“…Finally, individuals embedded in small networks reported significantly fewer deviant acts and exposure to deviant behavior online compared to those in medium and large networks. This is consistent with the results of Meldrum and Clark (2013) who found that time spent socializing with online peers was associated with an increase in delinquent behavior.…”
Section: Effect Of Exposure Across Network Sizesupporting
confidence: 92%
“…Previous research has shown socializing online with peers and exposure to deviant behaviors are both associated with offending (McCuddy & Vogel, 2014;Meldrum & Clark, 2013;Miller & Morris, 2014). Although scholars have begun to focus attention on this relatively new form of socialization, the mechanisms through which social learning operates in online environments remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations